2023
DOI: 10.1002/anr3.12244
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose sevoflurane co‐administered with propofol‐based general anaesthesia obliterates intra‐operative neurophysiological monitoring in an infant

H. Nakahari,
N. C. T. Wilton,
M. Ikeda
et al.

Abstract: SummaryThe influence of general anaesthetic agents on intra‐operative neurophysiological monitoring in neonates and infants has rarely been reported. Propofol‐based anaesthesia is recommended to avoid suppression of neurophysiological monitoring. However, the administration of propofol in children undergoing prolonged procedures, especially those younger than six months, should be carefully controlled due to the potential risk of propofol infusion syndrome. Adding a small dose of inhalational anaesthetic can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“… 3 In contrast, we reported a case of an infant that showed the eminent suppression of intraoperative MEPs induced by administering low-dose sevoflurane (0.10–0.15 age-adjusted MAC) with propofol-based anaesthesia. 7 Another study suggested that younger children (less than 3 years of age) require greater stimulating voltage during IONM due to the immaturity of the central nervous system, which may be more sensitive to anaesthetics compared with adults. Disappearance of IONM can occur with low-dose anaesthetics in this paediatric population, potentially leading to misleading surgical strategies, which is detrimental to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 In contrast, we reported a case of an infant that showed the eminent suppression of intraoperative MEPs induced by administering low-dose sevoflurane (0.10–0.15 age-adjusted MAC) with propofol-based anaesthesia. 7 Another study suggested that younger children (less than 3 years of age) require greater stimulating voltage during IONM due to the immaturity of the central nervous system, which may be more sensitive to anaesthetics compared with adults. Disappearance of IONM can occur with low-dose anaesthetics in this paediatric population, potentially leading to misleading surgical strategies, which is detrimental to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously reported the case of an infant whose MEP was significantly suppressed when sevoflurane, with an age-adjusted MAC of 0.10–0.15, was combined with a propofol-based TIVA. 7 Another case series of 19 infants retrospectively evaluated the impact of various anaesthetic regimes on MEP. The study demonstrated that adding even low-dose sevoflurane to propofol-based TIVA suppressed MEP in infants.…”
Section: Introductionmentioning
confidence: 99%